Emerging Technologies in Data Mining and Information Security Proceedings of IEMIS 2018, Volume 2 - Abraham, Ajith; Dutta, Paramartha; Mandal, Jyotsna Kumar; Bhattacharya, Abhishek; Dutta, Soumi (Advances in Intelligent Systems and Computing,, 2019)
The book features research papers presented at the International Conference on Emerging Technologies in Data Mining and Information Security (IEMIS 2018) held at the University of Engineering & Management, Kolkata, India, on February 23-25, 2018. It comprises high-quality research by academics and industrial experts in the field of computing and communication, including full-length papers, research-in-progress papers, case studies related to all the areas of data mining, machine learning, IoT and information security.